2018
DOI: 10.1016/j.dib.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Dataset of spray deposit distribution in vine canopy for two contrasted performance sprayers during a vegetative cycle associated with crop indicators (LWA and TRV)

Abstract: In 2016, spray deposit measurements have been carried out according to ISO22522:2007 on a vine estate (Domaine Mas Piquet, 15 ha, Languedoc). On this estate, plots vigor ranges from low to medium compared to other vineyards. On 4 days (28th April, 25th May, 23rd June and 18th July 2016), spray deposition has been measured on 5 plots of different vine varieties chosen for their distinct vigor. Two different sprayers have been used: a low performance sprayer (pneumatic arch sprayer used every 4 rows) and a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…1). These results align with those reported by Codis et al , 65 who used a vineyard pneumatic arch sprayer passing every four rows, and who found that canopy deposition in the full growth stage varied significantly according to canopy depth and row side. Here, even though the two different nozzles employed in the CP configuration produced very similar droplet size spectra (Table 1), 45 the mean deposition and its homogeneity were among the lower values.…”
Section: Resultssupporting
confidence: 92%
“…1). These results align with those reported by Codis et al , 65 who used a vineyard pneumatic arch sprayer passing every four rows, and who found that canopy deposition in the full growth stage varied significantly according to canopy depth and row side. Here, even though the two different nozzles employed in the CP configuration produced very similar droplet size spectra (Table 1), 45 the mean deposition and its homogeneity were among the lower values.…”
Section: Resultssupporting
confidence: 92%
“…This normalization process was adapted to consider the effect of the volume rate on the results. Following previous research, 51 it was determined using Eqn ): d100=()dN×100/VR where d 100 is the deposit per 100 L applied per hectare (μg cm −2 100 L –1 ha −1 ) and d N is the normalized tracer deposit (μg cm −2 leaf).…”
Section: Methodsmentioning
confidence: 99%
“…Another aspect that should be noticed is that the most common pneumatic sprayers used in vineyards are those which have the capability to spray more than one row at the same time, known as multi‐row pneumatic sprayers ( e.g . in France, where pneumatic sprayers are widespread, they represent 70–80% of sprayers used in large vineyards) . These sprayers are equipped with two different types of pneumatic nozzles: (i) hand‐type nozzles, with individual air spouts disposed as ‘fingers’ of the main spout and whose mission is to spray the row next to the sprayer, and (ii) the cannon‐type nozzles, with a main wide spout with very high air velocity that aims at spraying the further row, i.e .…”
Section: Introductionmentioning
confidence: 99%